Road Safety Management Capacity Assessment for Vanuatu - World Bank (World Bank, Washington, DC, 2021)
This Road Safety Management Capacity Assessment (RSMCA) seeks to gain a broad understanding of the Government of Vanuatu's road safety management capacity to support its plans to improve road safety outcomes throughout the country. The RSMCA follows the seven critical road safety institutional management functions (Bliss and Breen 2013) to identify key challenges and provide recommendations for improvement in road safety management, and similarly addresses the Safe System pillars for the interventions level. The seven institutional management functions include: results focus, coordination, legislation, finance and resource allocation, promotion and advocacy, monitoring and evaluation, and research and development of knowledge transfer. The Safe System pillars include road safety management, safe roads and mobility, safe vehicles, safe road users, post-crash care, and safe speeds. The RSMCA’s alignment with both the road safety institutional management functions and the Safe System Approach in turn aims to help the Government of Vanuatu to prioritize targeted next steps to address road crash death and serious injury in the country.